Diamagnetic repulsion of particles for multilaminar flow assays. Issue 126 (10th December 2015) - Tarn, Mark D.; Elders, Luke T.; Peyman, Sally A.; Pamme, Nicole
Abstract : A continuous multilaminar flow reaction was performed on functionalised polymer particles via diamagnetic repulsion forces, using a simple, inexpensive setup. Abstract : We demonstrate diamagnetic repulsion forces for performing continuous multilaminar flow assays on particles based on their intrinsic properties and with a simple setup. The platform could be applied to sandwich assays on polystyrene particles, and to cell-based assays via their suspension in biologically benign magnetic media.